The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.18778/0867-5856.32.1.09
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing MICE destination revisit intentions: A literature review

Abstract: The relationship between push and pull factors with the intention to revisit a destination has often been investigated in the context of general tourism. Not much is known on the factors influencing MICE destination revisit intentions, despite the numerous socioeconomic benefits that many countries have received from the MICE tourism business. This article attempts to fill the gap of knowledge by critically reviewing the literature using the integrative review approach. By reviewing, critiquing and synthesizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 138 publications
0
8
0
Order By: Relevance
“…Yoo and Chon (2008) indicated that numerous motivational factors drive MICE travellers' decisions and behaviours while Anas et al (2020) stated that motivational factors determine the success of MICE event. The motivational push and pull factors can be used to predict travellers' intent to attend or return to MICE events while Ramadan and Kasim (2022) revealed that the push and pull factors strongly influence an attendee's intention to revisit the same MICE event. Consequently, it is reasonable to assume that when push-and-pull travel motivations are combined, the likelihood of returning to a MICE destination increases; thus, it is essential to understand such events from the perspective of MICE attendees.…”
Section: Business Event Motivationmentioning
confidence: 99%
See 4 more Smart Citations
“…Yoo and Chon (2008) indicated that numerous motivational factors drive MICE travellers' decisions and behaviours while Anas et al (2020) stated that motivational factors determine the success of MICE event. The motivational push and pull factors can be used to predict travellers' intent to attend or return to MICE events while Ramadan and Kasim (2022) revealed that the push and pull factors strongly influence an attendee's intention to revisit the same MICE event. Consequently, it is reasonable to assume that when push-and-pull travel motivations are combined, the likelihood of returning to a MICE destination increases; thus, it is essential to understand such events from the perspective of MICE attendees.…”
Section: Business Event Motivationmentioning
confidence: 99%
“…Destination attractiveness also plays an important role in maximizing the economic benefits yielded from event attendance (Hashemi et al, 2020). Ramadan and Kasim (2022) have also declared that a destination that provides various attractions inspires event planners to host MICE activities there and entices travellers to revisit it. Furthermore, a destination that provides more attractions encourages MICE tourists' decisions to revisit it in the future (Hashemi et al, 2018).…”
Section: Destination Attractionmentioning
confidence: 99%
See 3 more Smart Citations